Effect of Different Support Morphologies and Pt Particle Sizes in Electrocatalysts for Fuel Cell Applications. (14th October 2010) - Sevjidsuren, G.; Zils, S.; Kaserer, S.; Wolz, A.; Ettingshausen, F.; Dixon, D.; Schoekel, A.; Roth, C.; Altantsog, P.; Sangaa, D.; Ganzorig, Ch.
Abstract : The performance of a low temperature fuel cell is strongly correlated with parameters like the platinum particle size, platinum dispersion on the carbon support, and electronic and protonic conductivity in the catalyst layer as well as its porosity. These parameters can be controlled by a rational choice of the appropriate catalyst synthesis and carbon support. Only recently, particular attention has been given to the support morphology, as it plays an important role for the formation of the electrode structure. Due to their significantly different structure, mesoporous carbon microbeads (MCMBs) and multiwalled carbon nanotubes (MWCNTs) were used as supports and compared. Pt nanoparticles were decorated on these supports using the polyol method. Their size was varied by different heating times during the synthesis, and XRD, TEM, SEM, CV, and single cell tests used in their detailed characterization. A membrane-electrode assembly prepared with the MCMB did not show any activity in the fuel cell test, although the catalyst's electrochemical activity was almost similar to the MWCNT. This is assumed to be due to the very dense electrode structure formed by this support material, which does not allow for sufficient mass transport.